A facile route to enhance the mobility of MoTe2 field effect transistor via chemical doping - Iqbal, Muhammad Waqas; Elahi, Ehsan; Amin, Aliya; Aftab, Sikandar; Aslam, Imran; Hussain, Ghulam; Shehzad, Muhammad Arslan (Superlattices and microstructures, 2020)
Modulating electrical characteristics is essential to attain a progressive performance of electronic devices such as field effect transistors (FETs). Chemical doping is very beneficial technique which is so simple and cost effective than other methods used in electronic devices for improvement of electrical characteristics. Here we report the effect of chemical doping with dopant tetracyanoquinodimethane (TCNQ) for the multilayer (ML)-MoTe2 field effect transistor (FET) to control its electrical properties. The threshold voltage (Vth) is shifted from negative to positive back gate voltage which shows p-type doping, furthermore, it was confirmed by Raman spectroscopy, the peak A1g is shifted towards higher wave number showing p-type doping effect in MoTe2 FET. Moreover, the full width at half maximum (FWHM) is reduced and the intensity ratio of the characteristic peaks (A1g and E12g) is decreased with respect to reaction time. The electrical measurements revealed improved current on/off ratio from 105 to107, mobility from 26.2 cm2/V s to 178.73 cm2/V s and charge carrier density from 3.41 × 1012 cm−2 to 7.9 × 1012 cm−2. These results offer the possibility of employing MoTe2 FETs in electronics. •Chemical doping of MoTe2 via tetracyanoquinodimethane.•The results were confirmed by Raman spectroscopy.•Improved current on/off ratio from 105 to107.•Mobility enhanced from 26.2 cm2/V s to 178.73 cm2/V s.